The Role of Stakeholders as Disaster Communicators at Disaster-Prone Tourist Attraction Objects - Adhianty Nurjanah; Nano Prawoto; Riski Apriliani; Chalila Raihan Nabilazka (Universitas Muhammadiyah Yogyakarta, 2023)
Indonesia is located in a disaster-prone region that can result in human casualties, property losses, environmental damage, and even impacts on the tourism sector. The provinces of Yogyakarta and Bali are vulnerable areas with tourist attractions (TAIs). Disaster communication becomes a crucial aspect that must be addressed to reduce disaster risks and their impacts. This research aims to analyze the role of stakeholders in implementing disaster communication at TAIs to achieve sustainable tourism. The results of this research indicate that three categories of stakeholders play crucial roles in disaster communication at TAIs. Primary stakeholders include local communities, local governments, and BPBD. Secondary stakeholders include the Ministry of Tourism, Non-Governmental Organizations, BASARNAS, TNI, and POLRI. Moreover, a key stakeholder identified in this study is the Indonesian Hotel and Restaurant Association (PHRI), which plays a significant role as a direct communicator responsible for managing and assisting tourists during disasters in ODTW areas.